RANCANG BANGUN APLIKASI INVENTORI DENGAN METODE PULL INVENTORY PADA PERUSAHAAN PERANGKAT JARINGAN - Nicholas, Martinez; Lee, Francka Sakti (Infotech: Journal of Technology Information, 2025)
A network equipment company specializing in the provision of switches and servers still faces challenges in stock management because the recording of outgoing goods and inventory withdrawal transactions is still done manually using notebooks and Excel. This condition causes problems such as delays in data updates, difficulties in monitoring stock availability in real time, and the risk of discrepancies between data and conditions in the warehouse. The objective of this research is to design and implement a web-based inventory application using a pull inventory approach, where stock is recorded only upon actual demand from projects or customers. This strategy helps reduce the likelihood of overstocking or understocking. Based on testing results, the developed application can support the recording of outgoing goods, provide real-time availability information, and generate useful reports for management, thereby supporting the efficiency, accuracy, and integration of the company's business processes.